Analisis Pelayanan Traveloka.com Terhadap Industri Pariwisata - Anggi Ramadan Kurniawan; Ragil Timur; Muhammad Naufal Miftahul Hakim; Tata Sutabri (International Forum of Researchers and Lecturers, 2024)
The analysis of Traveloka.com's services in the tourism industry encompasses various aspects, including usability, service quality, customer loyalty, and the influence of service quality on customer loyalty. The usability analysis of Traveloka.com's website revealed a high level of usability, as evidenced by efficiency, memorability, error rate, and user satisfaction. However, the study also identified areas for improvement, particularly in terms of system accessibility, privacy, and efficiency, which significantly impact customer satisfaction. Furthermore, the influence of service quality on customer loyalty was found to be significant, indicating the importance of continuous improvement in service quality to maintain and enhance customer loyalty. This research aims to provide a comprehensive understanding of Traveloka.com's services and their impact on the tourism industry, offering insights for the company's development and the advancement of the overall tourism sector.